2018
DOI: 10.1177/1464419318801732
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses of the elasto-plastic oblique contact-impact with vibration response

Abstract: Contact-impact between different surfaces is a ubiquitous phenomenon especially in the mechanical systems. Previous work of authors indicated that the effect of longitudinal and/or transverse vibration response during the motion and dynamic modeling cannot be neglected for the elasto-plastic contact-impact events. In this study, further analyses were performed to characterize the contribution of longitudinal and transverse vibration responses during the elasto-plastic oblique contact-impact, and the formula to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This is because when the markers are coplanar, the homogeneous matrix can not be solved using the least squares method due to the lacking information. However, more markers means a lot of work to gain the coordinate data and the least squares method involves numerical computations such as high‐order matrix inversion, iteration and singular‐value decomposition, which results a low positioning efficiency. On the other hand, the solution of TCR needs at least three markers.…”
Section: Mathematical Methodsmentioning
confidence: 99%
“…This is because when the markers are coplanar, the homogeneous matrix can not be solved using the least squares method due to the lacking information. However, more markers means a lot of work to gain the coordinate data and the least squares method involves numerical computations such as high‐order matrix inversion, iteration and singular‐value decomposition, which results a low positioning efficiency. On the other hand, the solution of TCR needs at least three markers.…”
Section: Mathematical Methodsmentioning
confidence: 99%
“…A MATLAB program has been developed to analyze the captured video images. 39,40 After some sample tests, we select the frame rate of 30/s to capture the needle motion. Each pixel in each frame is assigned its corresponding gray-scale value ranging from 0 to 255, with the value 0 representing pure black and 255 representing pure white.…”
Section: Methodsmentioning
confidence: 99%
“…Published amounts of research indicated that the effect of longitudinal and/or transverse vibration response during the motion and dynamic modeling can not be neglected for the elasto-plastic contact-impact events (Bazrafshan et al, 2014;Shafei et al, 2018). Authors previous works had done a quantitative analysis for mechanical vibration of the impacting object during impact events, and the longitudinal and transverse vibration responses were found to effect the normal and tangential velocities of the contact point after the impact, respectively.…”
Section: Dynamic Model With Vibration Responsementioning
confidence: 99%
“…Contact-impact is a particularly salient phenomenon which plays an important role pervasive in many applications involving the design and analysis of mechanical system, such as robotics (Banerjee et al, 2017;Flores-Abad et al, 2014), iron and steel metallurgy (Y. , vehicles (Yuan et al, 2016), civil structures (H. , composite structures (Mao et al, 2017;Park, 2017), and many other fields (Brake, 2015), since it affects motion parameters of the impacting object (e.g. rebound linear and an-gular velocity), contact force, and indentation deformation involving its patterns etc (Dong et al, 2018;Ghaednia et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%